Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi yang Meninggal Dunia - Shalahudin Serba Bagus; Adam Wildan Mubarak (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
According to the law, the perpetrators of criminal acts of corruption can be held accountable through the heirs of the criminals who died through civil lawsuits. However, in practice there are conflicting principles of criminal law due to the transfer of the lawsuit into a civil lawsuit. Just like the responsibility that should be criminal liability will become civil liability. The analysis in this paper explains what is unclear about religious blasphemy and links it to the principle of legality. The sources used are not only primary sources such as statutory regulations, but also secondary sources such as journals or articles on the internet.